Impact of diet on renal stone formation - Solafa H Ghoneim; Hotoon Alghaythee; Bashair Alasmari; Osama Y Safdar (Journal of Family Medicine and Primary Care)
Background and Objectives: The incidence of kidney stones is increasing globally, with a preponderance in adults compared with that in adolescents and children. Dietary habits have been identified as significant contributing factors to kidney stone formation. This literature review aimed to explore the existing evidence on the impact of diet on renal stone formation. Methods and Study Design: We conducted a comprehensive literature review and included 81 studies published between 1999 and 2023, limiting the search to articles published in English. The extracted data were analyzed to identify common themes, trends, and patterns related to the impact of diet on renal stone formation. We investigated the influence of dietary habits on the risk of nephrolithiasis. Results: Although the role of fluid intake in relation to stone formation is clear, existing evidence on how different types of beverages (coffee, tea, fruit juices, and soft drinks) affect kidney stone formation is conflicting. Other factors such as protein, sodium chloride, calcium, oxalate, fat, and carbohydrate intake have also been discussed as contributors to nephrolithiasis. Thus, diet should be appropriately modified to reduce the risk of stone formation in susceptible individuals. A history of nephrolithiasis has been found to increase the risk of both chronic kidney disease and end-stage renal disease. The review acknowledges the limitations inherent in conducting a literature review, including the potential for publication bias and the reliance on available published studies. Conclusions: These findings highlight the importance of understanding and preventing nephrolithiasis.